Neuro-oncology - Packer, Roger J., 1951-; Schiff, David, 1959- (Neurology in practice (Series), 2012)
The aim of the Neurology in Practice series is to provide a clinical 'in the office' or 'at the bedside' guide to effective patient care for neurologists in practice and in training. The tone will be practical, not academic. The working assumption is that readers want to know what (and what not) might or should be done, without over emphasis on the why. That said, it is important to review the crucial basic science necessary for effective diagnosis and management, and to provide reminders in the context of the practical chapters. The books will not be heavily referenced, in line with a more.